Preventing Chaotic Motion in Tapping-Mode Atomic Force Microscope - Rodrigues, Kleber dos Santos; Balthazar, José Manoel [UNESP]; Tusset, Angelo Marcelo; de Pontes, Bento Rodrigues [UNESP]; Bueno, Átila Madureira [UNESP] (Springer Nature, 2014)
During the last 30 years the Atomic Force Microscopy became the most powerful tool for surface probing in atomic scale. The Tapping-Mode Atomic Force Microscope is used to generate high quality accurate images of the samples surface. However, in this mode of operation the microcantilever frequently presents chaotic motion due to the nonlinear characteristics of the tip-sample forces interactions, degrading the image quality. This kind of irregular motion must be avoided by the control system. In this work, the tip-sample interaction is modelled considering the Lennard-Jones potentials and the two-term Galerkin aproximation. Additionally, the State Dependent Ricatti Equation and Time-Delayed Feedback Control techniques are used in order to force the Tapping-Mode Atomic Force Microscope system motion to a periodic orbit, preventing the microcantilever chaotic motion.
Keywords: Atomic Force Microscopy; Chaos; Nonlinear control systems; State Dependent Ricatti Equation; Time-Delayed Feedback